Pancasila sebagai sistem etika normatif: evaluasi kritis atas implementasi nilai-nilainya dalam kehidupan sosial - Widyawati, Ririn (Maliki Interdisciplinary Journal, 2026)
This article analyzes the role of Pancasila as a normative ethical system and its relevance in contemporary Indonesian society. Although Pancasila serves as the nation’s moral foundation, guiding behavior, policymaking, and character development, its practical implementation often diverges from its ideal principles. Social issues such as intolerance, declining solidarity, inequality, and persistent corruption reveal significant gaps between Pancasila’s ethical ideals and everyday realities. Globalization, rapid information exchange, and external cultural influences add further challenges to sustaining these values. Using a literature review and ethical analysis of each principle, the article assesses the extent to which individuals, institutions, and the government internalize the values of Divinity, Humanity, Unity, Democracy, and Social Justice. The analysis shows that despite Pancasila’s continued recognition as a shared foundation, its application is hindered by weak moral leadership, low social discipline, insufficient ethical education, and a fragile legal culture. The article proposes strengthening Pancasila-based character education, increasing public ethical awareness, promoting social values through literacy programs, and ensuring stronger institutional commitment to applying Pancasila consistently through concrete actions and policies. These efforts are expected to enhance Pancasila’s role as an effective ethical guide and provide stronger foundation for building a fair, cohesive, and culturally resilient society.